Empowerment Of Health School Unit Officers to Carry Out Acupressure and Self-Suggestion in Overcoming Adolescent Dysmenorrhea - I Gusti Agung Manik Karuniadi; Luh Putu Widiastini; I Gusti Gede Mayun Surya Darma (Universitas STRADA Indonesia, 2026)
The School Health Unit (UKS) is a cross-sectoral initiative aimed at improving students’ health knowledge, fostering healthy behaviors, and enhancing physical, mental, and social well-being among school-age children. The role of UKS cadres is essential in ensuring the effective implementation of school health programs. One of the major health challenges faced by adolescents today is reproductive health problems, particularly dysmenorrhea. According to the World Health Organization (WHO, 2020), approximately 90% of adolescent girls experience dysmenorrhea. Simple non-pharmacological methods, such as acupressure and self-suggestion, can be applied to reduce menstrual pain. This training program was designed to improve the knowledge and practical skills of UKS cadres in managing dysmenorrhea, enabling them to educate and support their peers. The training methods included lectures, demonstrations, and problem-solving sessions. The activity was conducted on May 4, 2024, and involved 40 UKS officers and one supervisor. The results showed a significant improvement in participants’ knowledge and skills about acupressure and self-suggestion in overcoming dysmenorrhea. Posttest findings indicated that 77.5% of participants had good knowledge of dysmenorrhea management, 70% were able to correctly perform self-suggestion techniques, and 95% successfully demonstrated acupressure practices. In contrast, pretest results revealed that all participants (100%) had no prior knowledge of these techniques. Overall, the training effectively enhanced both cognitive understanding and practical skills of UKS cadres in managing dysmenorrhea, highlighting the importance of integrating complementary therapies into school-based health programs.